Dual Vocational Training (Journal of Parents and Teachers, 2012)
Although much progress has been made in recent years, vocational training continues to be the subject of social discredit. In addition, it has a very high dropout rate and ratio, due to the tight budget that is given to it.
Keywords: Vocational Training; Training Cycles; Education.